Questioning Bioethics: AIDS, Sexual Ethics, and the Duty to Warn - Ainslie, Donald C. (The Hastings Center report, 1999)
Bioethicists have virtually assumed that Tarasoff generated a duty to warn the sexual partners of an HIV-positive man that they risked infection. Yet given the views of sex and of AIDS that have evolved in the gay community, in many cases the parallels to Tarasoff do not hold. Bioethicists should at the least attend to the community's views, and indeed should go beyond doing mere “professional ethics” to participate in the moral self-exploration in which these views are located.